2012
DOI: 10.1111/j.1365-2982.2012.01947.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between baseline impedance levels and esophageal mucosal integrity in children with erosive and non‐erosive reflux disease

Abstract: In children with GERD baseline impedance levels are not useful in predicting reflux-induced ultrastructural changes in the esophageal mucosa, despite their ability to discriminate between NERD and ERD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 39 publications
7
65
0
Order By: Relevance
“…8 More recently, in addition to the traditional MII-pH variables, a lower oesophageal impedance baseline (IB) has been taken into greater consideration as it appears to increase the sensitivity of MII-pH monitoring. [9][10][11] To our knowledge, this new parameter has been assessed in GERD patients with typical symptoms, but its capacity to diagnose reflux disease in suspected GERD-related CC patients has not yet been established. Empirical trials with proton pump inhibitors (PPIs) have gained considerable relevance in the routine management of patients with cough, but their role in the diagnosis of GERD is limited as the response of CC to PPIs is still widely debated and the currently available data have led to considering it as unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…8 More recently, in addition to the traditional MII-pH variables, a lower oesophageal impedance baseline (IB) has been taken into greater consideration as it appears to increase the sensitivity of MII-pH monitoring. [9][10][11] To our knowledge, this new parameter has been assessed in GERD patients with typical symptoms, but its capacity to diagnose reflux disease in suspected GERD-related CC patients has not yet been established. Empirical trials with proton pump inhibitors (PPIs) have gained considerable relevance in the routine management of patients with cough, but their role in the diagnosis of GERD is limited as the response of CC to PPIs is still widely debated and the currently available data have led to considering it as unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] In this study, the mean nocturnal baseline impedance (MNBI) values were assessed on the same site as pH monitoring (above LES 5 cm) and in the first stable 60-second times in every hour during the night when the individuals take supine position (Fig. 2).…”
Section: Twenty-four-hour Multichannel Intraluminal Impedance-ph Monimentioning
confidence: 99%
“…(2) We could not suggest the difference of BILs according to the types or severity of symptoms. (3) We were also unable to demonstrate macroscopic or microscopic mucosal changes during measurement even though studies have shown that BILs correlate with macroscopic and microscopic changes in the esophagus [2,4,5,14,15]. (4) We did not perform esophageal manometery in all patients.…”
Section: -H Z5 Bil (ω) 24-h Z5 Bil (ω)mentioning
confidence: 88%
“…Except during reflux episodes and swallows, the esophageal lumen remains collapsed and the metallic rings are in close contact with the esophageal mucosa; the resulting baseline impedance level (BIL) is determined by the intrinsic electrical conductivity of the surrounding esophageal wall [1,2]. Previous studies have suggested that BIL are related to esophageal acid exposure and pathological changes in the esophageal mucosa, thus serving as a potential marker of mucosal integrity [2][3][4][5]. Recent studies have also investigated the role of BIL in predicting the proton pump inhibitor (PPI) response in patients with GERD-related chronic cough or functional heartburn [1,6].…”
Section: Introductionmentioning
confidence: 98%